Hepatitis B seroprevalence in hematological oncology patients - Turken, Melda; Köse, Şükran; Özkan Acar, Ayşe; Ceylan, Cengiz; Albayrak, Hazal; Arkalı, Eren (The European Research Journal, 2020)
Objectives: Hepatitis B virus (HBV) infection is still a serious public health problem today. Many factors such as frequent blood transfusion, hemodialysis, sexual contact, sterilization in surgical procedures, etc. are involved in the transmission of hepatitis B virus. In our study, HBV seroprevalence was evaluated retrospectively in order to provide vaccination of anti-HBs negative patients and to determine HBV prophylaxis in patients with hematological malignancy. Methods: A total of 499 patients were included in the study. HBsAg, anti-HBs, anti-HBc IgG, anti-HDV, HBV DNA values were measured by ELISA (enzyme-linked immunosorbent assay, Liason, Diasorin, Italy) with Real-Time PCR (Cobas-Tagman, Roche Switzerland) and recorded. The obtained datas were evaluated by SPSS for Windows 15.00 statistical program. A value of p